Vitamin D Receptor Gene Polymorphisms in Multiple Sclerosis Susceptibility: Updated Systematic Review and Meta-Analysis - Han Yang; Baarid Luqman Hamidi; Esti Nur Ekasari; Krisandi Hartanto; Rudi Ilhamsyah (Magna Neurologica, 2026)
Background: The relationship between Vitamin D Receptor (VDR) gene polymorphisms and the risk of developing Multiple Sclerosis (MS) has been explored in numerous studies. However, the results were inconclusive. Therefore, this study aimed to investigate the relationship between VDR gene polymorphisms and susceptibility to MS. Objective: This study aimed to systematically evaluate the association between Vitamin D Receptor (VDR) gene polymorphisms and susceptibility to Multiple Sclerosis (MS) through a meta-analysis of existing studies. Methods: This study is a meta-analysis conducted in accordance with the PRISMA guideline. The literature search was conducted using the PubMed and Google Scholar databases from January 2014 to December 2024. Studies included in this meta-analysis were assessed using the Newcastle-Ottawa Scale (NOS). The association between VDR polymorphisms and the risk of MS was evaluated using pooled odds ratios (ORs) and 95% confidence intervals (CIs). Results: Six studies (868 cases/982 controls) were included. The TaqI polymorphism showed that TT vs TC + CC was associated with reduced risk of MS (OR 95% CI = 0.43 [0.21 - 0.86], p = 0.02), while CC vs TT + TC was associated with an increased risk of MS (OR 95% CI = 1.89 [1.51 - 2.36], p < 0.00001). T vs C was associated with reduced risk of MS (OR 95% CI = 0.69 [0.49 - 0.98], p = 0.04) while C vs T was associated with an increased risk of MS (OR 95% CI = 1.45 [1.02 – 2.05], p < 0.04). Conclusion: In summary, our meta-analysis revealed a significant association between VDR gene polymorphism and MS susceptibility in certain genetic models of the VDR gene.